BIOLOGIC ARMAMENTARIUM IN PSORIASIS - Pai, Ganesh; Sashidharan, Nithin (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Psoriasis is an autoimmune disease and further classed as a chronic inflammatory skin condition serving as global burden. Moderate to severe psoriasis can be treated with conventional therapies. Less efficacy, poor patient compliance and toxicity issues were the major problems associated with conventional therapies. The introduction of biologic therapy has great impression on psoriatic treatment duration and enhanced quality of life in psoriasis patients. The new biologic therapies are tailor made medications with goal of more specific and effective treatment; less toxicity. The biologic therapy is aimed to target antigen presentation and co-stimulation, T-cell activation and leukocyte adhesion; and pro-inflammatory cascade. They act as effective and safer substitute to traditional therapy. Secukinumab, certolizumab, itolizumab, golimumab, ustekinumab, adalimumab, infliximab etanercept, alefacept etc. are the approved biologic with global market. This review briefs about psoriasis pathogenesis, traditional treatments and biologic therapies potential.